Age and Caries Status of Children at the First Dental Visit in a Tertiary Care Hospital: A Cross-sectional Study - Malla, Manisha; Dikshit, Parajeeta; Limbu, Senchhema; Khanal, Sunita (Journal of Institute of Medicine Nepal, 2023)
Introduction Infant’s oral health is a vital part of their overall general health. An early first dental visit can influence the child's future oral health. The objective of this study was to assess the average age, reason, and caries status of children on their first dental visit at a tertiary care center in Kathmandu. Methods A cross-sectional observational study was conducted among the children aged 0-14 years visiting the outpatient department of Kantipur Dental College. A Validated questionnaire was provided to the parents visiting with the child and dental checkup was carried out in their first dental visit. Results Out of 334 children a total of 43 (12.9%) visited by 3 years of age and only 9 (2.7%) children visited by 1 year of age. Majority of children were of age 4-6 years (n=127) with a mean age of 6.71±2.95 years. The most common chief complaint for their first dental visit was decayed tooth (n=95, 28.4%), followed by pain (n=93, 27.8%) and 4 of them (1.2%) visited for routine check-up. Conclusions The majority of the children made their first dental visit too late. Children delaying their first dental appointment had much greater dental caries experience. Dental caries and associated complications were the primary reasons for the child's first dental appointment.